UJI AKTIVITAS ANTIOKSIDAN KOMBINASI ESKTRAK METANOL DAUN REMEK DAGING (Hemigraphis colorata W.Bull) DAN DAUN KRATOM (Mitragyna speciosa Korth) - Nur Aina; Chairul Saleh; Eva Marliana (JURNAL ATOMIK, 2025)
Antioxidant activity test of a combination of methanol extracts of meat remek leaves (Hemigraphis colorata w. bull) and kratom leaves (Mitragyna speciosa Korth) using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) silencing method with vitamin C as a positive control was analysed by UV-Vis spectrophotometry. The methanol extract of remek leaves contains flavonoids, triterpenoids/steroids and phenolic compound while the methanol extract of kratom leaves contains triterpenoids, flavonoids, alkaloids, saponins and phenolic. The combination of the two extracts gave the highest % inhibition in the 1:1 ratio. The IC50 values of methanol extracts of meat remek leaves, kratom leaves are 70.61; 33.43 ppm indicating antioxidant activity in the strong and very strong categories and the combination is 38.08 indicating the combination index is strong antagonis